PolyDiethyleneglycol–bisallyl carbonate matrix transparent nanocomposites reinforced with bacterial cellulose microfibrils. (August 2017) - Kunjalukkal Padmanabhan, Sanosh; Esposito Corcione, Carola; Nisi, Rossella; Maffezzoli, Alfonso; Licciulli, Antonio
Graphical abstract: Highlights: Novel transparent BC/DEAC nanocomposite synthesized by photo polymerization. Transparency obtained for nanocomposite is 88% at wavelength of 550 nm. Composite shows tensile strength of 130 MPa and a Young's Modulus of 6.4 GPa. Strain at failure around 3.7%, indicating ductile behavior of the composite. Abstract: Transparent nanocomposite films were prepared using bacterial cellulose (BC) as reinforcement and diethylene glycol bis(allyl carbonate) polymer (DEAC) as matrix by vacuum infiltration and UV polymerization. The BC/DEAC nanocomposites exhibit excellent transparency up to 88% at wavelength of 550 nm. The uniform dispersion of resin in BC 3D network was evidenced from SEM and ATR-FTIR analyses, confirms the complete photo-polymerization of diethylene glycol bis(allyl)carbonate monomer to Poly (diethylene glycol bis(allyl carbonate) in BC network. The BC/DEAC composites have good mechanical properties, reaching a tensile strength of 130 MPa and a Young's Modulus of 6.4 GPa. Applying a micromechanic modeling approach, the elastic modulus of the composite was used in order to determine the average aspect ratio of BC fibers. These flexible transparent BC/DEAC composite films can be considered as functional films for optoelectronics application.